Green Synthesis of Gold/Silver Hybrid Nanostructures for Surfaceenhanced Raman Scattering Spectroscopy - Chen, Chung-Yu; Lin, Yang-Wei (Current Nanoscience, 2014)
Tea-gold nanosponges (T-Au NSs), tea-silver nanoparticles (T-Ag NPs), and tea-gold/silver nanosponges (TAu/ Ag NSs) synthesized by mixing a tea infusion with gold (silver) ions were demonstrated. UV-Vis spectroscopy, transmission electron microscope (TEM), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), and powder X-ray diffraction (XRD) analysis were used to characterize as synthesized nanomaterials. Thereafter, the potential for use of the T-Au NSs, T-Ag NPs, and T-Au/Ag NSs in surface-enhanced Raman scattering (SERS) applications was investigated. The T-Au NSs provided a more intense SERS signal than the T-Ag NPs because of extremely intense local electromagnetic fields. In addition, the SERS enhancement factor for the T-Au NSs was further enhanced when Ag NPs were adsorbed on their surface.
Keywords: Green synthesis nanostructures